The Urgency of Halal Cosmetics (Halal Cleanliness) as One of The Sharia Tourism Travel Packs in Mojokerto - Mohammad Farih Fahmi; Rahma Sandhi Prahara; Binti Muta Farida (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Abstract Many natural attractions have stray dogs or pets that threaten the sanctity and comfort of Muslim tourists. In this regard, it is necessary to have halal cosmetics or halal cleaners as items that must be carried (travel packs) to anticipate when exposed to heavy impure to facilitate purification for Muslim tourists. Halal cleanlines or halal cosmetics need to be studied and analyzed for their urgency for the development of shariah tourism, especially in Mojokerto. The problems in this article are related to (1) How do Muslim tourists view mughaladzah impure in Mojokerto (2) Need to review halal cleanlines from a fiqh perspective (3) Trying to study and understand the level of urgency of halal cleanlines for Muslim tourists at natural attractions in Mojokerto. The method in this article is examined qualitatively with a phenomenological approach and case studies. The result of this study is that there is an urgent need to take advantage of halal clenlines for tourists in Mojokerto, this is supported by the permissibility of shariah cosmetics from a fiqh perspective so that it is better to provide it for tourist attractions in Mojokerto.